When a Virgin is not a Virgin - Lindhard, Tina (Advances in Social Sciences Research Journal, 2018)
My fascination with the Pythia began several years ago when I was writing a paper on different ways of knowing. Although the Pythia is surrounded in myth and has been written about by numerous authors both in the past and present, it seems to me she still has a story to tell which has not been touched on before. The Pythia was the priestess at Delphi and among other things, she had to be a virgin (pathenos), or at least originally. We also know that inscribed on the forecourt temple of Apollo was the maxim "Know Thyself". When we put these aspects together with the non-denominational method of meditation used by early cults in the Mediterranean area and other parts of the world known as Prayer of the Heart, a different meaning of the word virgin starts to reveal itself. This also suggests that these priestesses might have been mystics trained in an esoteric tradition, which leads to Self-discovery or the Godliness of humans.